Application of Organoid Models in Prostate Cancer Research - Zhou, Ligui; Zhang, Caiqin; Zhang, Yongbin; Shi, Changhong (Frontiers in Oncology, 2021)
Complex heterogeneity is an important characteristic in the development of prostate cancer (PCa), which further leads to the failure of known therapeutic options. PCa research has been hampered by the current in vitro model systems that cannot fully reflect the biological characteristics and clinical diversity of PCa. The tumor organoid model in three-dimensional culture retains the heterogeneity of primary tumor tissues in vitro well and enables high-throughput screening and genome editing. Therefore, the establishment of a PCa organoid model that recapitulates the diverse heterogeneity observed in clinical settings is of great significance for the study of PCa. In this review, we summarize the culture conditions, establishments, and limitations of PCa organoids and further review their application for the study of pathogenesis, drug screening, mechanism of drug resistance, and individualized treatment for PCa. Additionally, we look forward to other potential developmental directions of PCa organoids, such as the interaction between prostate cancer tumor cells and their microenvironment, clinical individualized treatments, heterogeneous transformation model, tumor immunotherapy, and organoid models combined with liquid biopsy. Through this, we provide more effective preclinical experimental schemes using the PCa organoid model.